(untitled) - Elseth, Gerald D. (Minneapolis/St. Paul, 1995)
This text , for a one-semester general genetics course for science majors, integrates the molecular and classical (Mendelian) approaches to genetics and takes an analytical approach, emphasizing problem solving and the analysis of research data.
Keywords: Genetics,Di truyền học